PENGARUH MODAL INTELEKTUAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA BUMN DI INDONESIA - Budianto Budianto; Zainal Putra; Eka Suci Wahyuni (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2018)
The main problem to be studied in this research is whether the variable of intellectual capital and profitability give positive influence in increasing company value in Indonesia Stock Exchange (IDX). The purpose of this research is to test empirically the influence of intellectual capital and profitability to company value. The population in this research are State-owned Enterprises (BUMN) listed in Indonesia Stock Exchange in the year of observation 2014 until 2016. Total population are 60 observation (20 companies x 3 years). Data used in this research are balanced panel data. The analysis method that is applied in this research is multiple regression analysis. The results of this research show that simultaneously intellectual capital and profitability have an effect to firm value. Partially, intellectual capital has a positive but not significant effect to firm value, while profitability have a positive and significant effect to firm value.